PUBLIC COLUMN AND REPRESENTATION IN DISCOURSE FIGHT CAMPAIGN NEWS OF INDONESIA PRESIDENT ELECTION IN 2014 - Pelenkahu, Noldy; Sulistyanto, Ari; Marentek, Fredy (IJRDO - Journal of Social Science and Humanities Research, 2018)
This study aims to describe the discourse fight campaign of Indonesia President election in 2014 and the impact of the mass media as the public column. The unit analysis of the study is the campaign news headline of Indonesia President election in 2014 of Seputar Indonesia and Media Indonesia newspapers. Van Dijk discourse analysis model was applied in the study. The research result showed that in the construction process, when the news goes to reductor level which had been done by the juornalists was always changed and suit to the character and media policy including the policy of the tittle statement and the language used. The newspapers have become different and provocative. So, in the discourse fight in Indonesia President ellection in 2014, there were representations to the candidates which was done by both of the mass media, and then went to the actors’ charater assassination and the distortion of the public column become not authentic. This was because of the mass media in their news had taken sides the candidate who is being the prominent figure.